Keefektifan Model Pembelajaran Realistic Mathematics Education (RME) Terhadap Kemampuan Pemecahan Masalah Matematika - Rambe, Juli Asmida; Erika, Erika (Pusdikra-Publishing.com, 2025)
The background that drives this research is the results of students' mathematical problem solving abilities which are still low and there are still many students who have not reached the KKM of 65 and the use of learning models that are less varied is the reason for researchers to carry out research in class V of Almusabbihin Elementary School The objectives in this study are This study aims to determine (1) the average class value of the mathematical problem solving ability of grade V students of Almusabbihin Elementary School reaches 65. (2) The mathematical problem solving ability of students who are given the RME learning model is better than before treatment. This type of research uses experimental research methods with Pre Experimental Design One-Group Pretest-Posttest Design. The study population was all fifth grade students of Almusabbihin Elementary School. The sample taken was 34 fifth grade students of Almusabbihin Elementary School using purposive sampling technique. Data collection instruments used math problem solving ability test instruments and observation sheets. Data analysis used, quantitative analysis of the right one-party t test. The calculation results obtained, the average class value of the mathematical problem solving ability of fifth grade students of Almusabbihin Elementary School reached KKM 65 as evidenced by the average initial score of 34.12 to 76.32 and classical learning completeness of 0% to 88.24%, there was a higher increase in postest scores than pretest scores. Students' math problem solving ability is better than before with a tcount of 12.358> ttable of 1.997. So, the Realistic Mathematics Education (RME) learning model is effective on mathematical problem solving of fifth grade elementary school students.